Student Perceptions of the Use of the Nahwu Mabda'i Book in Nahwu Learning in the Arabic Language Education Study Program FAI-UMM - Mochammad Firdaus; Ahmad Fatoni (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The goals of learning Arabic which is increasingly developing encourage the emergence of adjustments and development of nahwu science both from the material aspect as well as the learning methods and strategies. One of the compulsory subjects in the Arabic Department of the University of Muhammadiyah Malang, is the Nahwu 1 course. The Nahwu Mabda'i as a textbook is designed in such a way as to provide formulas to make it easier for readers to understand and memorize important principles in Arabic grammatical science. The purpose of this study was to determine student perceptions of the use of the Nahwu Mabda'i book in nahwu learning at the Arabic Department of the University of Muhammadiyah Malang. This research is a survey research with a qualitative approach. The data analysis technique used is a qualitative data analysis technique consisting of data collection, data reduction, data presentation, and making conclusions. The results of this study; (1) students' perceptions of the science material in the Nahwu Mabda'i book are quite positive, marked by their perceptions of the Nahwu 1 course presented; (2) Students feel that there is convenience in the form of selection and gradation in the Nahwu Mabda'i book because it is in accordance with the level of mental, emotional, social abilities, and the needs of the target audience.